EFEKTIFITAS PENGAWASAN KHUSUS OLEH INSPEKTORAT KABUPATEN SIGI - Ruddin, Azhar (Katalogis, 2015)
This study aims at determining whether the Special Surveillance conducted by Inspectorate of District Sigi has been going well or effectively. This research is a case study with a qualitative approach. The determination of research location and key informants were implemented purposively. The gathered data were analyzed in stages based on the information data of the informant that were obtained through observation, interviews and documentation. The result shows that of the three indicators to measure the effectiveness of Special Surveillance carried out by Inspectorate of District Sigi using the theory H. Emerson i.e. achievement of surveillance goal, achievement of surveillance target, and punctuality of surveillance, two indicators; achievement of surveillance target, and punctuality of surveillance are not running effectively. Meanwhile, the achievement of surveillance goal factor has been running well or effectively because this factor illustrates that in doing Special surveillance, Inspectorate has followed the mechanism and the investigator team always take an understanding of the examined object and also use their professionalism in determining the content form and communication intensity so that the examined objects immediately do improvements as directed by the investigator team.